Evaluation of therapeutic effects of Crocin in patients with polycystic ovary syndrome: A randomized Double-Blind clinical trial - Fatemeh Saghafi; Atiyeh Javaheri; Farhad Mohammadi; Nooshin Hatamizadeh; Fatemeh Khanizadeh; Mahdieh Safakish; Adeleh Sahebnasagh (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Polycystic ovary syndrome (PCOS) is the most common endocrine-metabolic disorder in women of reproductive age. Crocin is known as the main component of saffron, which has antioxidant properties and has the ability to scavenge free radicals. Considering the pathophysiology of PCOS and also the anti-inflammatory and antioxidant properties of crocin in improving insulin resistance, we aimed to evaluate the efficacy of the combination of crocin and metformin compared to metformin alone in PCOS patients. Methods This study is a prospective, double-blind randomized controlled clinical trial. Fifty patients with PCOS and hirsutism were included from Baqaipour Obstetrics and Gynecology Clinic in Yazd and randomly assigned into the two study arms of control group [metformin and placebo (n = 25)] or intervention group [metformin and crocin (n = 25)]. Patients were administered crocin 15 mg tablets once a day in combination with metformin 500 mg twice a day for 12 weeks to complete three full periods of the monthly cycle. The studied endpoints were evaluated at the beginning and end of the study. Results Crocin significantly improved the serum level of follicle-stimulating hormone (FSH) (P = 0.048) and Ferriman- Gallwey score (P = 0.042) at day 90. Furthermore, crocin group had a significant improvement in terms of acne severity at the end of the study (P = 0.03), so that none of the patients in the crocin group had severe acne at the end of the study. However, the comparisons between two groups were not statistically significant for other evaluated outcomes including fasting blood sugar (FBS), dihydroepiandrosterone-sulfate (DHEA-S), luteinizing hormone (LH), dermatology life quality index (DLQI), and blood pressure (BP) at the end of the study. Conclusion In the present study, concurrent use of crocin along with metformin was significantly effective in ameliorating the unpleasant side effects of PCOS, including hirsutism and acne, and increasing FSH sex hormone levels in patients with PCOS. Trial registry date 26/08/2021, Trial Registry number: IRCT20210730052027N1.